Sintesis Hidroksiapatit Dari Precipitated Calcium Carbonate (PCC) Cangkang Telur Ayam Ras melalui Proses Presipitasi - Agustiyanti, Rini Dwi; Azis, Yelmida; Helwani, Zuchra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Hydroxyapatite is high biactive dan bioafinity ceramic materials. Hydroxyapatite also known osteoconductive, non-toxic, and non-immunogeic. So that there are many application ofhydroxyapatite such as catalyst, fertilizer industry and pharmacy product, protein cromatography application, water treatment, bone and teeth repair. In this research, hydroxyapatite synthesised from PCC of chicken’s egg shell by using precipitation methodwith variation of pH (9, 10, and 11) and stirring speed (200, 250, and 300 rpm). Hydroxyapatite that acquired has been analyze by using FTIR, XRD, SEM-EDX, dan BET. From FTIR analysis best hydroxyapatite acquired by synthesis using pH 11 for stirring speed200 rpm, pH 9 for stirring speed 250 rpm, and pH 11 for stirring speed 300 rpm. From XRD analysis acquired hydroxyapatite with best crystalinity if it comparred with standardhydroxyapatite and smallest crystal size in pH 11 and stirring speed 300 rpm that is 23,07 nm. From SEM-EDX analysis known that acquired hydroxyapatite from synthesis in pH 11and stirring speed 300 rpm has agglomarate shape with particle size 62,5 nm and molar ratio 1,41. The result of BET analysis show that total surface area of hyroxyapatite was 28,406m2/gKeywords: agglomerate, hydroxyapatite, bioctive, stirring, pH, precipitation